PENDAMPINGAN SISWA DALAM MELATIH KEMAMPUAN BAHASA INGGRIS BERBASIS LANGUAGE FOCUSED LEARNING DI SMA NEGERI 4 SUNGAI PENUH - Mudra, Heri; Musdizal, Musdizal; Putri, Aisyah Latifah (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2021)
English learning is applied in schools to develop students' knowledge, language skills, and positive attitudes towards English. The skills in learning English that should be mastered are: a) listening, b) speaking, c) reading, and d) writing. The four types of skills have different levels of knowledge, so they can be taught in different ways. To master these four skills, students must first master the language component, also known as language-focused learning, which consists of vocabulary, grammar, and pronunciation. The problems experienced by students of SMA Negeri 4 Sungai Penuh in learning English include (1) Students' understanding of English language material is still lacking, (2) lack of guidance on the essential components of learning English, (3) still lack practical activities in learning English and (4) decreasing students' interest in learning English. The methods implemented are the lecture method, cooperative learning, student-centered learning, and interaction methods. The results of community service show that the students of SMA Negeri 4 Sungai Penuh get an increase in knowledge, which can be seen from the results of the pre-test in the poor category and the post-test results in the medium category. From these results, the Community Service team concluded that language-focused learning-based English assistance increased students' interest in learning English. They already have a basic knowledge of English based on language-focused learning to improve the four skills: listening, speaking, reading, and writing. This community service activity is expected to provide broad insight for students and the school, especially in learning English.